2016
DOI: 10.1111/andr.12169
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional association between physical activity and serum testosterone levels in US men: results from NHANES 1999–2004

Abstract: Background Testosterone levels and physical activity (PA) each play important roles in men’s health, but the relationship between the two remains unclear. Methods We evaluated the cross-sectional association between self-reported total PA and serum testosterone levels in 738 men (mean age 42.4 yrs, range 20-≥85yrs) who participated in NHANES 1999–2004. We compared geometric mean testosterone concentrations measured by RIA and calculated the odds ratio (OR) of having low or low normal testosterone (≤3.46 ng/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 52 publications
2
21
3
Order By: Relevance
“…Univariate analysis in our study revealed that independent risk factors of CVD, including BMI, HDL, triglyceride, diabetes, MET scores and tobacco use, were associated with serum testosterone levels. Furthermore, multivariate logistic regression analysis suggested that a BMI !35, HDL <0.91, diabetes and MET score <12 were correlated with TD, which was in agreement with previous studies, indicating that testosterone negatively correlated with BMI and diabetes but positively correlated with HDL and physical activity [38][39][40]. In the participants of the study, there was no association between age and low testosterone serum concentrations beside in men >70 years (Table 3), which is in line with a previous study in which male total testosterone concentrations showed increasing variance but no decline after age of 40 years [41].…”
Section: Discussionsupporting
confidence: 91%
“…Univariate analysis in our study revealed that independent risk factors of CVD, including BMI, HDL, triglyceride, diabetes, MET scores and tobacco use, were associated with serum testosterone levels. Furthermore, multivariate logistic regression analysis suggested that a BMI !35, HDL <0.91, diabetes and MET score <12 were correlated with TD, which was in agreement with previous studies, indicating that testosterone negatively correlated with BMI and diabetes but positively correlated with HDL and physical activity [38][39][40]. In the participants of the study, there was no association between age and low testosterone serum concentrations beside in men >70 years (Table 3), which is in line with a previous study in which male total testosterone concentrations showed increasing variance but no decline after age of 40 years [41].…”
Section: Discussionsupporting
confidence: 91%
“…6,27 A low level of testosterone can result in a reduced sex drive, increased body fat, 6,25 decreased motivation, 38 caused sleep problems, 39 and showed chronic low energy. 40,41 In order to overcome the physical energy reduction caused by low levels of testosterone, exercise could be the answer. Several studies demonstrated that chronic exercise increased physical energy 41,42 and increased brain plasticity, leading to increased cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year-long NHANES study included 738 participants, who were classified in three tertiles, based on metabolic equivalent of task (MET) score, and according to the compendium of physical activities. No cross-sectional association was found between a greater physical activity and changes in basal plasma testosterone concentrations [ 28 ]. Houmard et al [ 29 ] showed that despite increasing endurance exercise’s frequency, duration, and intensity over 14 weeks (3–4 days/week, 30–45 min/day), no significant changes in the resting plasma testosterone concentrations were noted.…”
Section: Part 2: Changes In Basal Resting Testosterone Levelsmentioning
confidence: 99%